Evaluation of the Hypoglycemic and Hypolipidemic Potential of Extract Fraction of Quercus baloot Griff Seeds in Alloxan-induced Diabetic Mice - Hussain, Sheheryar; Jan, Farzana Gul; Jan, Gul; Irfan, Muhammad; Musa, Muhammad; Rahman, Shahid; Ali, Niaz; Hamayun, Muhammad; Alrefai, Abdulwahed Fahad; Almutairi, Mikhlid H.; Azmat, Rafia; Ali, Sajid (Current Pharmaceutical Design, 2024)
Introduction The discovery and development of new phytomedicines can be greatly aided by plants because of their tremendous therapeutic benefits, efficiency, cost-effectiveness, lack of side effects, and cheaper therapies. In this regard, Quercus baloot, generally known as oak, is used in folkloric medicine for treating and preventing various human disorders, including diabetes. Aim For this purpose, the present study aimed to evaluate crude methanolic extract and various fractions of Quercus baloot for antihyperlipidemic and antihyperglycemic potential followed by the analysis of active compounds. Methods The hypoglycemic and hypolipidemic activity was evaluated in Swiss male Albino mice by administering an oral dose of 150-300 mg/kg of Q. baloot extracts in alloxan induced diabetic mice for 14 days. Results The results revealed that crude methanolic extract at a dose of 300 mg/kg exhibited a significant reduction in the blood glucose level (198.50 ± 1.99 mg/dl) at day 14 and the same treatment significantly increased the body weight (31.26 ± 0.27 g) at day 14 in comparison to the control group. Moreover, the biochemical parameters were investigated which presented an increase in high-density lipids (HDL) (30.33 ± 0.33 mg/dl), whereas low-density lipids (LDL) showed a significant decrease (105.66 ± 0.26 mg/dl). Additionally, triglyceride levels 104.83 ± 0.70 mg/dl, and total cholesterol 185.50 ± 0.76 mg/dl are significantly decreased. In serum biochemical analysis creatinine and hepatic enzyme markers, like serum glutamate pyruvate transaminase (32.00 ± 0.36 U/mg), serum glutamate oxaloacetate transaminase (34.33 ± 0.61 U/mg), and alkaline phosphatase (157.00 ± 0.73 U/mg), were significantly reduced by the crude methanolic extract at a dose of 300 mg/kg as compared to the control group. The antioxidant enzymes like Superoxide dismutase (4.57 ± 0.011), peroxidases dismutase (6.53 ± 0.014, and catalase (8.38 ± 0.014) at a dosage of 300 mg/kg of methanolic extract exhibited a significant increase. The histopathological study of the diabetic heart, liver, and pancreas showed substantial restoration of damaged tissues in the methanolic extract 150 and 300 mg/kg treated group, which supports the effectiveness of Q. baloot seeds. The gas chromatography-mass spectrometry analysis of methanolic extract identified 10 antidiabetic active compounds in the Q. baloot seeds, validating the antihyperglycemic activity. Thus, methanolic crude extract at the doses 150 and 300 mg/kg of Q. baloot showed significant antihyperlipidemic and antihyperglycemic activities, which validate the folkloric utilization of Q. baloot as a remedy in diabetes. Conclusion In conclusion, the 300 mg/kg methanolic extract of Q. baloot has notable hypoglycemic and hypolipidemic potential, supporting the plant's traditional medicinal usage in the treatment of diabetes and its complications. Further studies are needed for the purification, characterization, and structural clarification of bioactive compounds.
Keywords: seeds; folkloric medicine; diabetes mellitus